2013
DOI: 10.1371/journal.pone.0077835
|View full text |Cite
|
Sign up to set email alerts
|

Manganese (Mn) Oxidation Increases Intracellular Mn in Pseudomonas putida GB-1

Abstract: Bacterial manganese (Mn) oxidation plays an important role in the global biogeochemical cycling of Mn and other compounds, and the diversity and prevalence of Mn oxidizers have been well established. Despite many hypotheses of why these bacteria may oxidize Mn, the physiological reasons remain elusive. Intracellular Mn levels were determined for Pseudomonas putida GB-1 grown in the presence or absence of Mn by inductively coupled plasma mass spectrometry (ICP-MS). Mn oxidizing wild type P. putida GB-1 had high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 68 publications
(65 reference statements)
2
35
0
1
Order By: Relevance
“…This is interesting to note, considering that both bacteria produce extracellular superoxide (Diaz et al ., ) and Mn(II) can scavenge superoxide (Archibald and Fridovich, ; Barnese et al ., ; Hansard et al ., ). Further, a recent study has shown a connection between intracellular Mn(II) and oxidative stress in another Mn(II) oxidizing bacterium, Pseudomonas putida GB‐1 (Banh et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…This is interesting to note, considering that both bacteria produce extracellular superoxide (Diaz et al ., ) and Mn(II) can scavenge superoxide (Archibald and Fridovich, ; Barnese et al ., ; Hansard et al ., ). Further, a recent study has shown a connection between intracellular Mn(II) and oxidative stress in another Mn(II) oxidizing bacterium, Pseudomonas putida GB‐1 (Banh et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…What function does Mn(II) oxidation play in the bacterial community such that the cost of secreting large oxidase enzymes is evolutionarily affordable? Mn(II) oxidation has been shown to protect P. putida GB-1 from hydrogen peroxide (11). In the closely related plant-beneficial strain P. putida KT2440, deletion of the mopA homolog PP2561 resulted in increased sensitivity to compounds like tert butyl hydroperoxide (43), supporting a role for Mn(II) oxidation in the oxidative stress response.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidation reaction is thermodynamically favorable, raising the possibility that bacteria could derive energy from Mn(II) oxidation (10). Recent studies have also shown that Mn(II)-oxidizing bacteria exhibit increased resistance to the reactive oxygen species hydrogen peroxide (11). Nonetheless, the physiological function of bacterial Mn(II) oxidation remains unclear.…”
mentioning
confidence: 99%
“…Although Mn(IV) formation could generate energy for organisms, this has not been definitively shown for any organism (4,5). However, Mn oxidation was shown to increase the survival of Pseudomonas putida GB-1 in the presence of reactive oxygen species (ROS) (18). In addition, Mn oxidation has been speculated to provide other advantages to the cell, such as abiotic oxidation of refractory organic matter by Mn oxides (3) or controlling the availability of toxic metal ions (2,3,19).…”
mentioning
confidence: 99%